Kinesins and Myosins: Molecular Motors that Coordinate Cellular Functions in Plants - Nebenführ, Andreas (Annu Rev Plant Biol, 2018)
Kinesins and myosins are motor proteins that can move actively along microtubules and actin filaments, respectively. Plants have evolved a unique set of motors that function as regulators and organizers of the cytoskeleton and as drivers of long-distance transport of various cellular components. Recent progress has established the full complement of motors encoded in plant genomes and has revealed valuable insights into the cellular functions of many kinesin and myosin isoforms. Interestingly, several of the motors were found to functionally connect the two cytoskeletal systems and thereby to coordinate their activities. In this review, we discuss the available genetic, cell biological, and biochemical data for each of the plant kinesin and myosin families from the context of their subcellular mechanism of action as well as their physiological function in the whole plant. We particularly emphasize work that illustrates mechanisms by which kinesins and myosins coordinate the activities of the cytoskeletal system.